Evaluasi Kualitas Pendidik di Era Globalisasi (Current Research in Education: Conference Series Journal, 2022)
This study aims to be able to identify and evaluate the quality of educators in the era of globalization as well as to find out strategies that can be used to improve the quality of educators in the era of globalization. This research uses qualitative methods by finding and reviewing scientific literature from reliable and credible sources, as well as the results of the study. This research proves that the quality of educators in this era of globalization, especially in Indonesia, has not been able to answer the challenges and demands of globalization due to factors such as the quality of human resources, school facilities, curriculum quality and others.